Developing a methodology for assessing the risk of hostile takeover of a motor transport enterprise and measures to prevent it - Nesterenko, V. Yu.; Chevychelova, O. O.; Нестеренко, В. Ю.; Чевичелова, О. О. (Харківський національний автомобільно-дорожній університет, 2021)
Problem. Mergers and acquisitions are traditional processes of redistribution of property rights in a market economy. Mergers are often used by companies to gain control over larger market segments and increase performance efficiency. The acquisition process is not always desirable for the target company and is often used to establish control over its assets. Thus, the problems of assessing the risk of hostile takeover of the enterprise and its prevention are extremely rele-vant at the current stage, especially in the transport sector of Ukraine. Goal. The goal of the work is to develop the methodology for assessing the risk of hostile takeover of a motor transport enterprise and suggest methods for preventing its occurrence. Methodology. During the study, the following research methods have been used: analysis and synthesis, logical analy-sis. Information resources of the study are electronic information resources and periodic publi-cations. Results. The risk of hostile takeover of an enterprise is the probability that the enter-prise will become the takeover target through the legal actions and methods taken by the ac-quirer, but the acquisition procedure itself is against the wishes of the target’s board. The list of factors that determine the attractiveness of the potential acquisition target includes: the attrac-tiveness of the enterprise in terms of its financial results and performance, the enterprise is not public, it occupies a considerable market segment, the enterprise operates as a joint-stock com-pany, it is attractive in terms of further resale of its assets, the prospects of the industry in which the enterprise operates. According to the results of the studies assessing the risk level of hostile takeover of the group of motor transport enterprises, it has been revealed that 45% of enterpris-es are in the medium risk group. The following list of measures aimed at defending motor transport enterprises against hostile takeovers has been developed: the formation of optimal share capital structure; share consolidation when the majority shareholder holds the controlling interest; carrying out a sound dividend policy, the continuous monitoring of amounts and ma-turity dates of accounts payable, preventing the risk of arousing the counterparties’ interest in the resale of debt obligations of the enterprise to others. Originality. The methodology for as-sessing the risk of hostile takeover of a motor transport enterprise and reasonable measures to prevent its occurrence have been proposed. Practical value. The proposed recommendations can be used by the owners and management of motor transport enterprises to build an effective system for preventing potential hostile takeovers.
Розробка методики оцінювання ризику недружнього поглинання автотранспортного підприємства та заходи його попередження
Keywords: merger; hostile takeover; risk; motor transport enterprise; share capital; accounts payable; злиття; недружнє поглинання; ризик; автотранспортне підприємство; акціонерний капітал; кредиторська заборгованість; 658.15; 10.30977/AT.2019-8342.2021.49.0.07